Dual Inhibitors of Acetylcholinesterase and Monoamine Oxidase-B for the Treatment of Alzheimer’s Disease - Ayesha Asim; Michał K. Jastrzębski; Agnieszka A. Kaczor (Molecules)
Alzheimer’s disease (AD) is a multi-factorial neurodegenerative disease with a complex pathomechanism that can be best treated with multi-target medications. Among the possible molecular targets involved in AD, acetylcholinesterase (AChE) and monoamine oxidase B (MAO-B) are well recognized because they control the neurotransmitters responsible for memory processes. This review discusses the current understanding of AD pathology, recent advances in AD treatment, and recent reports in the field of dual AChE/MAO-B inhibitors for treating AD. We provide a classification of dual inhibitors based on their chemical structure and describe active compounds belonging to, i.a., chalcones, coumarins, chromones, imines, and hydrazones. Special emphasis is given to the computer-aided strategies of dual inhibitors design, their structure–activity relationships, and their interactions with the molecular targets at the molecular level.